The North seen by People from the South. Italian Explorers about the Arctic. The Journal of Giacomo Bove - Khachaturyan, Elizaveta (Nordlit, 2008)
The objects of my analysis are the travel writings and expedition reports of Italian Arctic explorers. In the present paper I will analyse the Journal of Giacomo Bove, who was a member of the Swedish Arctic expedition of the ship "Vega" (1878-79) headed by Nordenskjold (Il Passaggio del Nord-Est. Spedizione artica svedese della "Vega". Diario di Giacomo Bove. A cura del dott. A. Fresa, 1940, Memorie della R. Società Geografica Italiana, volume XIX. Roma.). One of the tasks given to Giacomo Bove by the Italian Geographic Society was to describe the expedition. One of the problems that Bove had to solve in this case was which words to use when speaking of an alien reality. This other reality was for him constituted not only by natural phenomena (like, i.e., fauna and flora, ice and weather), but also by an unfamiliar material culture (the life of the northern people), and by the life of the expedition.